THE EFFECTS OF SERVANT LEADERSHIP AND ETHICAL LEADERSHIP ON SATISFACTION WITH SUPERVISOR - Zakhyadi Ariffin (Universitas Lambung Mangkurat, 2023)
The purpose of this study was to investigate the effects servant leadership and ethical leadership on satisfaction with supervisor. This study uses a quantitative approach. The sample size in this study was 63. Respondents were employees of regional offices of national telecommunications companies in South Kalimantan province. Data analysis used multiple linear regression. All variables have been tested for validity and reliability. The results showed that servant leadership and ethical leadership had an effect on employee satisfaction with their supervisors. The novelty of this study examines the effect of ethical leadership on employee satisfaction with their supervisors